COMPARATIVE ANALYSIS OF CONSONANTS IN ENGLISH AND UZBEK LANGUAGES - Sharipova Yorqinoy (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This paper explores the comparative analysis of consonant sounds in English and Uzbek from a phonetic and phonological perspective. The study highlights both the similarities and differences in the articulation, classification, and distribution of consonants in these two languages. By examining voiced and voiceless consonants, place and manner of articulation, and specific phonological rules, the research aims to identify areas that may present difficulties for Uzbek learners of English. The findings of this paper contribute to improving pronunciation teaching strategies and enhancing phonetic competence among language learners.